The ecosystem approach as a framework for understanding knowledge utilisation - Haines-Young, Roy; Potschin, Marion (Pion, 2014)
The Ecosystem Approach is used to analyse four case studies from England to determine what kind of ecosystem knowledge was used by people, and how it shaped their arguments. The results are reported across decisions making venues concerned with: innovation; conflict management; maintenance of ecosystem function; and, recognising the environment as an asset. In each area we identify the sources and uses of conceptual, instrumental, political and social knowledge. We found that the use of these knowledges can benefit the process as well as the quality of outcomes, and so ‘add value’ to the decision making process. However, the case studies did not exhibit any simple linear-rational model of knowledge use. Ecosystems thinking took many forms and depended on different institutional settings. As an argument making device, the Ecosystem Approach must be seen in the context of a wider set of social and political processes, which involves a range of complex strategies and motives that explain the apparent ‘messiness’ of environmental decision making. The paper demonstrates that as conceptual framework, the ‘ecosystem approach’ provides a valuable theoretical template to help us discover how and what knowledge is used in deliberative styles of decision making.